(untitled) (ACTA MEDICA PERUANA, 2022)
Sagittal craniosynostosis is the premature closure of the sagittal suture, causing functional and structural alterations. The treatment is surgical, and there are currently various techniques, which require planning and training to achieve optimal results. We present the case of a 1-year-old male with abnormal anteroposterior growth of the skull, indicating brain tomography without contrast, showing sagittal synostosis. Surgical planning of the technique to be developed is carried out using a real-scale personalized 3D model. The patient progresses well and is discharged. Finally, essential 3D cloning technology for neurosurgical education and development allows access to high-precision, low-cost tactile models that improve the quality of craniosynostosis management.